Adolescent Access to Abortion Care in Canada: Age, Capacity and Parental Consent. - CATTAPAN, ALANA; HAMMOND, KATHLEEN; MCGRATH, ELEANOR (Healthcare Policy, 2025)
For adolescents seeking abortion care in Canada, clear information about age and parental consent requirements is not always available. This article details the state of age of consent law and policy across Canada, focusing on access to abortion care. It identifies three key concerns, namely, challenges with unclear or contradictory information, obstacles presented by having additional requirements for minors' consent and difficulties posed by restrictions that require parents and/or guardians to be involved in decision making. The article concludes with recommendations to reduce these barriers to care.